2023
DOI: 10.3390/biomimetics8010101
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intrusion of Anterior Teeth by Skeletal Anchorage in Deep Bite Patients; A Systematic Review and Meta-Analysis

Abstract: Background: Deep bite is known as one of the most common malocclusions, and its treatment and retention are often challenging. The use of mini-screws has been suggested as an ideal method for the intrusion of incisors in deep-bite patients. Still, there are conflicting reports regarding the superiority of this method compared to other common treatments. Aim: The aim of this systematic review and meta-analysis was to evaluate the effects of the intrusion of anterior teeth by skeletal anchorage in deep bite pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Through the process of growth and development, the skeletodental and soft-tissue components structurally adapt to one another to create a functionally balanced condition [64]. A shift in the mandibular muscular balance takes place because widening the bite is typically performed via protrusion of posterior teeth [13]. If the correction is to stay stable, either the musculature must adjust in some way to its new functional resting length or the bone arrangement must alter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the process of growth and development, the skeletodental and soft-tissue components structurally adapt to one another to create a functionally balanced condition [64]. A shift in the mandibular muscular balance takes place because widening the bite is typically performed via protrusion of posterior teeth [13]. If the correction is to stay stable, either the musculature must adjust in some way to its new functional resting length or the bone arrangement must alter.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the lower portion of the face, the anterior facial height is frequently tiny in such circumstances. The incisors' supraocclusion (overeruption), on the other hand, is indicated by dental deep bites [13] or infraocclusion (undereruption) of the molars or a combination of the two [14]. Alterations to the tooth morphologies, early loss of permanent teeth leading to a lingual collapse of the maxillary or mandibular anterior teeth, mesiodistal breadth of anterior teeth, and age-related natural deepening of the bite are other factors that might have an impact on this condition.…”
Section: Etiologymentioning
confidence: 99%
“…For those resulting from anterior dentoalveolar extrusion and vertical maxillary excess, it can be improved by the intrusion of maxillary anterior teeth [ 1 , 2 ]. Additionally, the deep overbite is a common malocclusion, which can affect facial aesthetics, occlusal function, and overall oral health [ 3 ]. In cases of skeletal Class II and vertical growth pattern with deep overbite, the intrusion of maxillary anterior teeth not only facilitates bite opening but also creates space for counterclockwise rotation of the mandible, which is crucial for the improvement of facial profile [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…J-hook headgear causes strong discomfort and requires patient compliance [ 4 ]. Other methods are less effective and may lead to the extrusion of posterior teeth [ 3 ]. Researchers have confirmed that the application of mini-implants can effectively facilitate the intrusion of maxillary anterior teeth and achieve true intrusion [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation